Evaluation of the new criteria of 2010 for diabetes mellitus: Japan Diabetes Society - Fujikawa, Rumi (Diabetol Int, 2016)
We investigated the characteristics of the new criteria for diabetes mellitus (DM) issued by the Japan Diabetes Society in 2010, which include HbA(1C) measurement, and differences between 1999 criteria, in order to indicate clinical caution points. If a person with fasting plasma glucose (FPG) ≥126 mg/dl or an oral glucose tolerance test (OGTT) 2-h value ≥200 and HbA(1C) ≥6.5 % is determined as having DM, the disease can be detected at a rate of ≥70 % in persons <60 years and at no more than 40–50 % in elderly persons. In longitudinal examination, we observed that individuals with DM with FPG ≥126 mg/dl and HbA(1C) ≥6.5 % obtained the same determination over time at a rate of nearly 90 %. The percentage of persons whose result shifted from normal type to DM was 3- to 4-fold lower than that of persons whose result shifted from normal type to diabetic type. Based on these results, measurement of FPG and HbA(1C) at the same time may be extremely effective in identifying DM, although we should pay attention to a higher likelihood that mild glucose metabolism disorders will be overlooked.